2015
DOI: 10.1037/pro0000024
|View full text |Cite
|
Sign up to set email alerts
|

Temperament traits, social support, and secondary traumatic stress disorder symptoms in a sample of trauma therapists.

Abstract: Secondary traumatic stress disorder (STSD) consists of identical symptoms as posttraumatic stress disorder (PTSD), but while PTSD originates from direct exposition to a traumatic event, STSD is a consequence of indirect exposure to trauma due to close personal contact with a trauma victim. This article examines the severity of STSD symptoms and their relationship to temperament traits and social support in a sample (N = 80) of trauma therapists in Poland. In our study, we controlled for demographic data, such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 56 publications
(77 reference statements)
2
23
1
2
Order By: Relevance
“…The phenomenon of STS has already been investigated for various professional groups, e.g. interpreters for refugees (Kindermann et al, 2017 ), trauma therapists (Hesse, 2002 ; Pearlman & Mac Ian, 1995 ; Rzeszutek, Partyka, & Gołąb, 2015 ), social workers (Lee, Gottfried, & Bride, 2018 ), combat veterans’ spouses (Waysman, Mikulincer, Solomon, & Weisenberg, 1993 ) and first responders (Greinacher, Derezza-Greeven, Herzog, & Nikendei, 2019 ). Furthermore, previous studies have suggested that ECDs are at risk of developing STS in consequence of their exposure to the graphic description of emergency situations during emergency calls (Miller, 1995 ; Shakespeare-Finch, Rees, & Armstrong, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The phenomenon of STS has already been investigated for various professional groups, e.g. interpreters for refugees (Kindermann et al, 2017 ), trauma therapists (Hesse, 2002 ; Pearlman & Mac Ian, 1995 ; Rzeszutek, Partyka, & Gołąb, 2015 ), social workers (Lee, Gottfried, & Bride, 2018 ), combat veterans’ spouses (Waysman, Mikulincer, Solomon, & Weisenberg, 1993 ) and first responders (Greinacher, Derezza-Greeven, Herzog, & Nikendei, 2019 ). Furthermore, previous studies have suggested that ECDs are at risk of developing STS in consequence of their exposure to the graphic description of emergency situations during emergency calls (Miller, 1995 ; Shakespeare-Finch, Rees, & Armstrong, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…In regard to the latter, it was demonstrated that especially a history of anxiety or depression can be associated with a higher symptom load after being indirectly exposed to traumatic material (Ensel & Lin, 2000 ; Orbach, Lamb, Sternberg, Williams, & Dawud-Noursi, 2001 ; Van der Kolk et al, 1996 ). In the occupational group of trauma therapists, a higher number of traumatized patients, low experience in trauma therapy, and high degrees of emotional reactivity were shown to be associated with higher rates of STS, while participating in clinical supervision, the availability of self-care techniques, and high degrees of sensory reactivity were associated with lower rates of STS (Chrestman, 1995 ; Creamer & Liddle, 2005 ; Figley, 2013 ; Rzeszutek et al, 2015 ). Furthermore, sociodemographic variables, such as younger age, female gender, lower educational achievement, as well as lack of social and familial support were found to predict higher STS symptom burden in various occupational groups (Adams, Matto, & Harrington, 2001 ; Baum, 2016 ; Choi, 2011 ; De Jong, van Sonderen, & Emmelkamp, 1999 ; Ensel & Lin, 2000 ; Lerias & Byrne, 2003 ; Rzeszutek et al, 2015 ; Zimering et al, 2003 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…"Experienced an event outside the range of usual human experiences that would be markedly distressing to almost anyone," (Figley, 1995, p. 8), such as sudden tragedy which could destroy the traumatized person's (TP) environs or a severe threat to TP. It can develop suddenly, in contrast to burnout (Figley, 1995;Rzeszutek, Partyka, & Gołąb, 2015); this is described as a critical incident (Salston & Figley, 2003). Similar to CF, but more exact terminology (Figley, 1995); STS is one element of CF (Stamm, 2010); psychological symptoms more present in STS than schema interruption in VT (Baird & Kracen, 2006); amount of exposure to clients, caseload, and cumulative impact increases the likelihood of STS (Baird & Kracen, 2006;Myers & Cornille, 2002;Wee & Myers, 2002); Most directly linked to the PTSD diagnostic framework (Devilly et al, 2009); Vicarious trauma (VT)…”
Section: Secondary Traumatic Stress Frameworkmentioning
confidence: 99%
“…Likewise, burnout is a construct that develops over time, with gradually emerging symptoms as the common etiology (Maslach, 2003). STS has been associated with a more sudden onset of symptoms (Benson & Magraith, 2005;Figley, 1999;Rzeszutek et al, 2015;Salston & Figley, 2003). It should be noted that STS might not occur quickly for everyone, but that a sudden onset is possible.…”
Section: Compassion Fatigue (Cf)mentioning
confidence: 99%